Implementasi metode flash card dan Padlet dalam meningkatkan kemampuan berbicara bahasa inggris siswa kelas X di MAN 1 Kota Probolinggo - Mahfudza, Fitria Zulaika Zulaika (Maliki Interdisciplinary Journal, 2025)
This study aims to improve the English speaking skills of tenth-grade students at MAN 1 Kota Probolinggo through the implementation of flash card and Padlet methods in learning recount texts (personal experiences). The study employs a Classroom Action Research (CAR) design conducted in two cycles. In the first cycle, the flash card method was used by having students randomly select cards and speak based on the keywords provided. The results revealed that most students struggled with vocabulary selection and lacked confidence in speaking. In the second cycle, the Padlet method was implemented by instructing students to first write their personal experiences on Padlet, then present them orally without reading from the text. The results showed a significant improvement in students’ speaking performance. They appeared more prepared, confident, and used a broader range of vocabulary. Based on observations and test results, the Padlet method proved to be more effective in enhancing students’ English speaking skills compared to the flash card method.